The management of science laboratory at senior high school in digital era - Evana, Yores; Fitria, Happy; Fitriani, Yessi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The problem in this research is how is the science laboratory management at SMA Negeri 4 Ogan Komering Ulu. The research objective was to identify and describe the science laboratory management at SMA Negeri 4 Ogan Komering Ulu. This study uses a qualitative approach which is an approach to the process of collecting data and information that is deep, detailed and systematic in order to understand the object of the research study. The results of this study generally concluded that the management of the science laboratory at SMA Negeri 4 Ogan Komering Ulu was good enough and supported science learning. This can be seen from the laboratory planning that has been implemented optimally even though there are still many limitations faced, the implementation of the planning has been carried out well, the budget for the laboratory is available even though it is not fully sufficient, the tools and materials in the laboratory are quite complete and has made innovations using virtual laboratories in science learning that are connected via the internet network.